A guideline on biomarkers in the diagnosis and evaluation in axial spondyloarthritis - Liu, Dong; Xie, Ya; Tu, Liudan; Wen, Xianghui; Lv, Qing; Liu, Budian; Yang, Mingcan; Wu, Xinyu; Zheng, Xuqi; Luo, Xiqing; Zhou, Liuzhong; Wu, Jialing; et al. (Frontiers in Immunology, 2024)
Objective: To develop a guideline for selecting biomarkers in the diagnosis and assessment in patients with axial spondyloarthritis (axSpA). Method: A joint effort was carried out by the core team, the literature review team and the multidisciplinary voting panel to formulate recommendations regarding biomarkers in axSpA, using an evidence-based and consensus-based strategy. Certainty of evidence and strength of recommendation were determined, and levels of agreement within the voting panel were calculated.Results: A total of 20 recommendations were formulated in this guideline, with levels of agreement ranging from 6.48 to 9.71. The two strong recommendations, HLA-B27 testing in patients suspected of axSpA and regular-interval monitoring of CRP/ESR represent the status quo of axSpA evaluation, while the 13 conditional recommendations represent the promising biomarkers with clinical utility in diagnosis, disease activity assessment, prediction of radiographic progression and therapeutic responses. This guideline does not dictate clinical choices of tests on axSpA, and decisions should be made based on comprehensive consideration of costs, accessibility, patients' values and willingness as well as the objective of testing in the local context. Conclusion: This guideline addresses the interpretation of the clinical significance of biomarkers in axSpA, and the biomarkers endorsed in this guideline composed a clinical toolkit for healthcare professionals to choose from.